2021
DOI: 10.1186/s12978-021-01072-4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase facility births and provision of postpartum care in sub-Saharan Africa: a scoping review

Abstract: Background Most maternal deaths occur during the intrapartum and peripartum periods in sub-Saharan Africa, emphasizing the importance of timely access to quality health service for childbirth and postpartum care. Increasing facility births and provision of postpartum care has been the focus of numerous interventions globally, including in sub-Saharan Africa. The objective of this scoping review is to synthetize the characteristics and effectiveness of interventions to increase facility births o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Furthermore, another integrative review concluded that poorly trained HCWs deter the utilisation of PNC services because their clients lose trust [ 25 ]. The provision of training could be viewed as a quest to guarantee quality PNC services which is another strategy recommended in the literature and has yielded improved rates of PNC attendance [ 26 ]. These pieces of training could be embedded as part of continuous professional development (CPD) for the HCWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another integrative review concluded that poorly trained HCWs deter the utilisation of PNC services because their clients lose trust [ 25 ]. The provision of training could be viewed as a quest to guarantee quality PNC services which is another strategy recommended in the literature and has yielded improved rates of PNC attendance [ 26 ]. These pieces of training could be embedded as part of continuous professional development (CPD) for the HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, then, other women could be trained to support other postpartum women with prior training and boundaries set in advance. Evidence shows that community-based health workers (CHWs) are integral to the provision of PNC services and their participation in the delivery has increased uptake [ 26 ]. Adoption of community midwifery assistants in Malawi could be a link that can be strengthened while including CHWs as well to take up some of these roles [ 28 ] with prior training on the specific postpartum assessments they need to conduct for the mother and newborn [ 10 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest proportion of deliveries in health facilities is in the North African region (84%), while the lower regions are the East and West African ones, with 51.2% and 51.4% deliveries at health institutions ( Table 4 ). In the West and Central African regions, the proportion of women receiving care from a professional at birth is also low [ 112 ]. Another problem in South and East Africa is the delay in accessing healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of recourses to maternal health care and the acceptability and affordability of maternal health services are factors in MM in Sub-Saharan countries [ 112 ]. Nevertheless, the main problem in Sub-Saharan Africa is not so much the accessibility of health services but that women seek care late in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…First, the MoH must be fully involved in the scale-up and use of this tool at the national level. The State's adoption of a health intervention would better guarantee its sustainability; however, this guarantee may be mainly based on financial resources ( 16 18 ). In addition, to ensure CT sustainability for FGF management, it is crucial to address the workload related challenge.…”
Section: Discussionmentioning
confidence: 99%